Strategi Guru Dalam Mengelola Risiko Gangguan Disiplin Dan Konsentrasi Belajar Siswa Perspektif Pendidikan Islam Di SD Negeri 12 Pemulutan Barat, Sumatera Selatan - Sri Eva Mislawaty (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2026)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in managing the risk of disciplinary disturbances and students' learning concentration at SD Negeri 12 Pemulutan Barat, South Sumatra. This research employed a qualitative approach with a case study design. The informants consisted of the principal and Islamic Religious Education teachers selected purposively. Data were collected through observation, in-depth interviews, and documentation and were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. The findings indicate that the forms of disciplinary and concentration disturbances include students talking during lessons, arriving late, not completing assignments, feeling sleepy, losing focus, and being easily distracted. These conditions are influenced by family environment, excessive gadget use, low learning motivation, and monotonous teaching methods. To manage these risks, teachers implemented various strategies, including creating a conducive classroom atmosphere, applying varied learning methods, providing educational sanctions, conducting interactive communication, and collaborating with parents. The study concludes that Islamic Religious Education teachers play strategic roles as murabbi, mu'allim, and muaddib in fostering discipline, responsibility, and self-control among students through exemplary conduct, habituation, and persuasive approaches to create a conducive learning environment.